Evolution mechanism of wind turbine wake structure in yawed condition by actuator line method and theoretical analysis. (1st April 2023) - Wang, Tengyuan; Cai, Chang; Wang, Xinbao; Wang, Zekun; Chen, Yewen; Hou, Chengyu; Zhou, Shuni; Xu, Jianzhong; Zhang, Yuning; Li, Qingan
Highlights: The wake deflection and distortion characteristics of Yawed wind turbine are analyzed. A new wake evolution mechanism of yawed wind turbine is revealed. Counter-rotating Vortex Pair plays a dominating role in wake evolution. A theoretical model for the Counter-rotating Vortex Pair is proposed. Abstract: Through deflecting the wind turbine wake and reducing the influence of wake effect, wind farm cooperative control can enhance the total power generation of wind farm. In addition to wake deflection, the wake of yawed wind turbine shows complex distortion characteristics, which cannot be explained sufficiently by traditional momentum conservation. In this paper, numerical simulation using Actuator Line Method and theoretical analysis were adopted to investigate the wake characteristics of NREL 5 MW wind turbine in yaw. The wake of yawed wind turbine shows a velocity deficit distribution with kidney-shape. Due to the periodic change of tip vortex shedding velocity, the vorticity carried by tip vortex changes periodically, leading to the formation of an asymmetric counter-rotating vortex pair (CVP), which induced the complex wake structure of yawed wind turbine. On this basis, a new theoretical model for the wake structure of yawed wind turbine is proposed, which can accurately predict the main characteristics of the CVP. This paper reveals the wake evolution mechanism of yawed wind turbine and establishes the corresponding theoretical model, which is conducive to the development of high-precision engineering wake model and the optimization of wind farm cooperative control.